WEED FLORA OF GLADIOLUS FIELDS IN DISTRICT KASUR, PAKISTAN - T. Riaz; S. N. Khan; A. Javaid (Journal of Animal and Plant Sciences, 2009)
District Kasur is the hub of Gladiolus cultivation in Punjab, Pakistan. Field surveys from 12 localities of the district were undertaken during 2005-06 and 2006-07 to study the distribution of various weed species in Gladiolus fields. Sixty weed species belonging to 24 angiospermic families were found growing in the fields of Gladiolus. Ageratum conyzoides L., Amaranthus viridis L., Coronopus didymus (L.) Sm., Chenopodium album L., Chenopodium murale L., Convolvulus arvensis L., Cypreus rotundus L., Cynodon dactylon Pers., Poa annua L., Oxalis corniculata L., Rumex dentatus L., Melilotus parviflora, L. Cenchrus pennisetiformis Hochest and Eragrostis poaeoides Beauv. were found to be the most prevalent weed species occurring in 90% or more studied areas during one or the other growing season. Frequently occurring weeds with absolute frequency above 40% were C. didymus, C. arvensis, R. dentatus, C. pennisetiformis and C. dactylon. R. dentatus was found to be the most frequently occurring and densely populated weed species with absolute frequency of 57% and absolute density of 1.2 during 2006-07 growing season. Other densely populated weed species with absolute density above 0.50 were A. conyzoides, C. didymus, C. arvensis, C. rotundus, Euphorbia prostrate, C. pennisetiformis and C. dactylon.
Keywords: Absolute frequency; Angiospermic; Density; Gladiolus; Weed species